Learning in social media for developing of nonformal education program - Elihami Elihami (Universitas Muhammadiyah Enrekang, 2023)
The emergence of social media has altered the landscape of human contact. Through the use of social media from the nonformal education department at Universitas Muhammadiyah Enrekang, educators have a rare opportunity to put the principles of social learning into practice. theory for improved learning and student engagement in a social media environment. This article synthesizes recent research on social learning theory and social media technology with an emphasis on how social media applications in the classroom could be utilized to boost students' motivation, memory, and attention as they relate to learning new information. Discussion of implications for practitioners is done in terms of the student, lesson, and faculty contexts.